Evangelisation, protest and ethnic identity: sixteenth century missionaries and Indians in Northern Amazonian Ecuador - Muratorio, Blanca (1984)
The native people of the Ecuadorian tropical forest have had almost 450 years of contact with different representatives of white colonial and post-colonial societies. Through these years, the presence of missionaries among the native groups has been the most pervasive. Missions have been consistently organized as institutions whose main objective was, at least until very recently, to radically change the natives’ world view and way of life. Until the State became interested in the economic resources and the potential for colonization of its Amazon region in the 1940’s, the missionaries practically maintained the monopoly of the task of ‘civilizing’ the different native groups and integrating them into the larger society.